Silence and praise rhetorical cosmology and political theology in the Book of Revelation - Hansen, Ryan Leif (Fortress Press, 2014)
"In Silence and Praise, Ryan Leif Hansen begins with the premise that cosmology is a central focus in John's Apocalypse. However, John's intention in reflecting theologically on the nature, existence, and destiny of the created world is not in order to explicate a stable system. Rather, John's cosmological thought is employed for persuasive purposes as an ethical and political critique of Roman imperial cultic discourse. Hansen seeks to read the contours of John's "rhetorical cosmology" and to understand the theological and political implications of its strategy"--back cover
Includes bibliographical references (pages 169-180) and index
Introduction -- "The apocalyptic technique" : how John's apocalypse makes meaning -- The war of worldcraft : John's cosmic rhetoric against Roman imperial cult discourse -- The three cycles of seven as object of interpretation -- Silence : the prayerful endurance and non-participation of the saints -- Praise : narrating the emergence of God's reign and the new creation -- Silence and praise : economic non-participation and narrating the new creation -- Toward an apocalyptic political theology
Keywords: Bibel -- Offenbarung des Johannes; Bible / Revelation / Criticism, interpretation, etc; Biblical cosmology; Politics in the Bible; Bibel; Reich Gottes; Kosmologie; Politische Theologie; Rome / In the Bible; Rom; Hochschulschrift